Reading comprehension assessment for student selection: advantages of text availability in terms of validity - Sedlmayr, Paul; Weissenbacher, Barbara (Frontiers in Education, 2025)
Reading comprehension assessments are widely used in university entrance exams across various fields. These tests vary in text content, answer format, and whether the text remains available while the questions are being answered. We explored how the availability of the text impacts the psychometric quality of the test and what is the best format for assessing reading comprehension in university admissions. We developed a test with four educational texts and 88 questions. A group of 107 university students was tested on two texts under two conditions: with and without text availability, using identical true/false questions for both scenarios. Results show similar difficulties in both versions, but slightly higher item-total correlations and internal consistencies in the text-unavailable condition, although this varied between texts. The text-available condition showed better validity, with expected correlations with participants’ verbal intelligence and language scores. Overall, allowing text access during the test appears to be advantageous for assessing reading comprehension in university admissions.